Nano-sized TiVH catalysts unlocking high-performance hydrogen storage in magnesium hydride - Jianbin Yang; Jiaguang Zheng; Changhai Wu; Haoran Shen; Deyu Tang; Chao Su; Panpan Zhou (Fuel, 2026)

Secondary forest succession shifts soil carbon priming from microbial to mineral control through dynamic microbe–mineral coupling - Panpan Wu; Jing Zhang; Xi'an Cai; Zhijian Mou; Yue Li; Wenjia Wu; Tengteng Li; Rong Mao; Zhanfeng Liu (Soil Biology and Biochemistry, 2026)

Light-driven photothermal micropump integrating pumping transport, hyperthermia, and membrane disruption for spatially selective bacterial elimination - Panpan Cao; Jianhua Zhang; Lu Liang; Meizhen Zou; Jianhong Wu; Yu-Qi Feng (Chemical Engineering Journal, 2026)

Reduction-Alkylation Proteome Profiling (RAPP): A novel strategy for proteome-wide target identification - Yiying Wu; Jingwen Yan; Yuting Chen; Guangyuan Liu; Yuran Wang; Qian Wang; Liangyu Pan; Yuyu Zhang; Panpan Zhang; Wei Zhang; Dezhi Kong (Analytica Chimica Acta, 2026)

Chitosan oligosaccharides reshape Penicillium digitatum infection responses in 'Harumi' fruit by reinforcing defense signaling and phenolic metabolism - Hengquan Wu; Xun Wang; Panpan Gao; Yating Wang; Tuan Wang; Changpin Chun; Yizhong He; Mingfei Zhang (Postharvest Biology and Technology, 2026)

Linking hydrological exchange and DOM transformation in a semi-arid river: Insights from isotopic and fluorescent fingerprinting - Yanyan Gao; Xinjie Xu; Panpan Tian; Hui Qian; Xiaoxin Shi; Zhiming Cao; Hao Huang; Jinkun Zhang; Zeyu Shi; Yixin Liu; Siqi Li; Yandong Ma; et al. (CATENA, 2026)

Rhizosphere microbiome drives selenium bioavailability: Mechanisms and implications for biofortification - Lin Wu; Panpan Han; Huimin Lu; Wensheng Zhang (Applied Soil Ecology, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Chemical weathering processes in the north-south transition zone of China: A case study from the Danjiang River Basin - Zhiming Cao; Hui Qian; Yanyan Gao; Kang Li; Panpan Tian; Weijie Zhao; Shuhan Yang; Xiaoxin Shi; Siqi Li; Yixin Liu; Puxia Wu; Yandong Ma (Journal of Environmental Sciences, 2026)

Lactiplantibacillus plantarum LP6490 alleviates PhIP-induced intestinal injury accompanied by changes in gut microbiota and short-chain fatty acid metabolism - Panpan Wang; Siwei Zhang; Ziwen Qü; Shuanglei Zhang; Yongning Wu; Yanbo Wang; Guoliang Li (Food Bioscience, 2026)

One-pot self-separating Janus hydrogel for wet tissue integration, hemostasis, anti-adhesion, and wearable biosensing - Wenhuan Huang; Yan Wang; Xiangcun Shang; Cong Li; Kaize Su; Dongli Li; Jingwei Jin; Panpan Wu; Keke Wu (Chemical Engineering Journal, 2026)

Reprogramming senescent granulosa cells for germ-cell generation - Dai Heng; Kairang Jin; Guoxing Yin; Chenglei Tian; Xiaoyan Sheng; Jiangtao Lu; Yiwei Wu; Xiaoying Ye; Panpan Shi; Huiyu Li; Chang Liu; Lin Liu; et al. (Science China Life Sciences, 2026)

TroIRF6, a teleost interferon regulatory factor of Golden pompano (Trachinotus ovatus), enhances antimicrobial defense and immune potentiation - Panpan Zhang; Zikai He; Guisen Chen; Ying Wu; Xiaoyuan Zheng; Jinge Wang; Zhenjie Cao; Chen Zhang; Jie Sun; Zhigang Tu; Yongcan Zhou; Yun Sun (Aquaculture, 2026)

Machine learning for the spatial prediction of soil and groundwater contamination: An integrative global review - He Wu; Zhuo Zhang; Panpan Wang; Chouyuan Liang; Yue Liu; Yakun Wang; Tianyi Wu; Han Zhang; Jie Ren (Journal of Hazardous Materials, 2026)

Wetland succession reshapes microbial degradation of plant- and microbial-derived carbon - Yunlong Zheng; Fangli Su; Haifu Li; Haoyu Wu; Panpan Cui; Fei Song (Journal of Environmental Management, 2026)

Corrosion-fatigue life prediction of high-strength steel wires based on reconstructed critical distance theory - Xing Yang; Jianguo Zhong; Jianwen Situ; Panpan Wu; Anye Xu; Zhonghong Dong (Engineering Structures, 2026)

High-entropy alloy intercalated montmorillonite for efficient photocatalytic methane oxidation to formaldehyde - Qian Liu; Tong Wu; Chun Yang; Panpan Gao; Xintong Yao; Songmei Sun (Chemical Engineering Journal, 2026)

FDEM-Based Investigation of Rockburst Mechanisms in a Deep Tunnel under Complex In-Situ Stress Conditions - Haoyu Han; Panpan Hu; Hongyuan Liu; Daisuke Fukuda; Jianbin Xie; Qianwen Wu; Zitang Wang; Yatao Yan; Huaming An; Yingyao Cheng (Geotechnical and Geological Engineering, 2026)
Rockbursts are critical geohazards during the construction of deep buried tunnels under high in-situ stress conditions. However, their accurate predictions and effective mitigations remain challenging in complex geo-stress environments. This study utilizes an in-house combined finite-discrete element method (FDEM) to conduct a case study on the rockbursts observed in a deep buried railway tunnel in southwestern China revealing their occurring processes and mechanisms under onsite high in-situ stress conditions. The model successfully reproduces the entire development process of typical rockbursts occurring on site, including fracture initiation and propagation, as well as fragment ejection and flyout, which is difficult to capture in field monitoring. The simulation results demonstrate that, due to the orientation of the in-situ stress, the rockburst initiates at the left spandrel of the tunnel and then progressively extends toward the tunnel crown and left sidewall, forming a V-shaped notch, which is consistent with field observations. Then, systematic parametric studies are conducted to further investigate the effects of lateral pressure coefficients and the deviation angle of in-situ principal stress orientations from the vertical direction on the rockburst behavior. It is found that the lateral pressure coefficient governs both the spatial location of the rockburst and the orientation of macroscopic fractures, while the deviation angle serves as a key factor controlling the migration of dominant rockburst damage zones along the tunnel profile. This study is expected to enhance the understanding of rockburst mechanisms in complex geo-stress environments and provide theoretical basis for risk assessment and support design of tunnels in deep underground.

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Identifying sources and quantifying contributions of plutonium in sediments of the Taiwan Strait - Panpan Yang; Jisheng Chen; Yiting Huang; Xiuli Yan; Wenting Bu; Ke Xiong; Cui Wang; Shuqin Tao; Junwen Wu (Journal of Hazardous Materials, 2026)

Waterlogging risk assessment of cotton in the Jianghuai region, China - Haoyu Ma; Hao Wu; Xudong Han; Min Xu; Xiaoping Chen; Zhuoyue Peng; Yuanning Wang; Panpan Wang; Yi Tang; Shiwen Min (European Journal of Agronomy, 2026)

Liquid crystal elastomer-based thermal switch enabled by shape memory effect for tunable thermal conductivity - Pengfei Huang; Panpan Yang; Xiaoting Lu; Hui Yang; Lili Fang; Kaiyuan Yi; Kun Wu; Jun Shi (Chemical Engineering Journal, 2026)

Dietary hydroxyproline and taurine interaction affected the anti-oxidation, muscle fiber growth, collagen metabolism, and muscle hardness of abalone Haliotis discus hannai - Heng Zhang; Mengxi Yang; Dong Huang; Zhenhua Wu; Keke Lei; Peng Chen; Pengfei Zhang; Panpan Yue; Kangsen Mai; Wenbing Zhang (Journal of Oceanology and Limnology, 2026)

Injectable nanocomposite depot with real-time ultrasound control of osteogenic drug release - Yu Shu; Xiang Zhang; Ruonan Jiang; Shunan Wang; Yin Yi; Wenting Du; Siyi Li; Yuanyuan Liu; Huimin Liang; Pengfei Zhou; Panpan Liang; Jinlin Song; et al. (Chemical Engineering Journal, 2026)

Ternary network derived from polyphenol-inspired sticky nanoparticle: nanofiltration separation efficiency and end-of-life membrane regeneration potential - Jiaying Yan; Panpan Wang; Ying Cao; Jinlong Zhu; Xingyan Jin; Luwei Li; Chuandong Wu; Hao Zhang; Hui Xie; Jun Ma (Water Research, 2026)

Unraveling the influence of storage condition on off-flavor generation in fried pepper (Zanthoxylum bungeanum Maxim.) oil during storage through molecular sensory science and simulation experiment - Tianyu Dong; Shuwei Wang; Panpan Wu; Jie Sun; Haitao Chen; Shuqi Wang (Food Chemistry, 2026)

ISTNet: a multi-scale transformer-based architecture for malaria cell classification - Panpan Wu; Xiuyan Gao; Hengyong Yu (Medical & Biological Engineering & Computing, 2026)

Development of advanced transition model for addressing spurious separation bubble in transitional flow simulations - Ning Li; Panpan Han; Qiao Ma; Xiaoping Qiu; Yunxiang You; Kaijian Wu (Ocean Engineering, 2026)

Hydrochemical evolution and surface water-groundwater interactions in a typical mountainous basin: Insights from multiple isotopes, chemical tracers, and multiple models - Zhiming Cao; Hui Qian; Yanyan Gao; Kang Li; Xiaoxin Shi; Siqi Li; Panpan Tian; Yixin Liu; Jinkun Zhang; Zeyu Shi; Puxia Wu; Yandong Ma (Journal of Environmental Chemical Engineering, 2026)

Pathogen-driven modulation of eight STATs in Cromileptes altivelis: Comparative analysis from homeostasis to immune activation - Panpan Zhang; Shuyi Lin; Zixin Xie; Guisen Chen; Zhenjie Cao; Chen Zhang; Jingqun Ao; Yongcan Zhou; Ying Wu; Yun Sun (Fish & Shellfish Immunology, 2026)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

The causal effect of natural killer cells on COVID-19 infection, hospitalization and severity - Kaili Yang; Jun Quan; Zhi Liu; Zebing Huang; Shuyi Wang; Jia Li; Aiming Wang; Li Wu; Songman Yu; Panpan Yi; Meifang Xiao; Yayu Chen; et al. (Inflammation Research, 2025)

Effects of vegetation cover and rock embedding landscape types and configurations on regulating runoff generation and sediment yields in karst slope under simulated experiment - Linlv Xiao; Rui Li; Feiyang Cai; Panpan Wu; Longhui Pan (Journal of Hydrology, 2025)

Molecular characterization and antibacterial function of the interleukin-8 in humpback grouper (Cromileptes altivelis) - Ying Wu; Jinge Wang; Ziyu Wang; Panpan Zhang; Han Zhang; Guotao Wang; Hong Chen; Zhenjie Cao; Chen Zhang; Jingqun Ao; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2025)

Electrically conductive and anti-inflammatory nerve conduits based on chitosan/hydroxyethyl cellulose hydrogel for enhanced peripheral nerve regeneration - Jiahui Song; Chenlong Liao; Zhengchao Yuan; Xiao Yu; Jie Cui; Yangfan Ding; Panpan Shang; Jinglei Wu; Binbin Sun; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Wenchuan Zhang; et al. (Carbohydrate Polymers, 2025)

Atraric acid activates the FoxO3a/PINK1/Parkin signaling pathway to suppress chronic intermittent hypoxia-induced cardiac oxidative stress, inflammatory responses, and NLRP3 inflammasome activation - Mengxin Li; Wanqi Wu; Boran Hu; Huizhen Chen; Jun Wang; Shasha Zhang; Tianyue Guan; Hujing Lu; Jiawen Zhou; Panpan Zhao; Yong Sun (Chemico-Biological Interactions, 2025)

Effects of daytime and nighttime warming on C: N: P stoichiometry in leaf-root-soil system and plant biomass - Bingheng Cheng; Qiang Yu; Zhengyan Lei; Panpan Zhao; Yuanhao Zhang; Qianfeng Yuan; Zhuoyi Wu; Biying Liu; Ting Zhou; Shaolin Peng (Plant and Soil, 2025)

Interaction effects of organic mulch application rates and rainfall intensities on soil and water loss in karst sloping farmlands: Insights from a laboratory simulation experiment - Panpan Wu; Rui Li; Feiyang Cai; Ling Xiong; Zhengyi Tang; Linlv Xiao (Soil and Tillage Research, 2025)

Porous MXene/transition metal dichalcogenide heterostructure anodes with accelerated charge transfer kinetics for high-energy and long-life sodium-ion hybrid capacitors - Mingming Gao; Jundong Shao; Ying Huang; Xinyi Duan; Sheng Yang; Faxing Wang; Feng Yu; Zaichun Liu; Yao Gao; Panpan Zhang; Yuping Wu; Xing Lu (Chemical Engineering Journal, 2025)

Remediation of lead-zinc-cadmium co-contaminated soil using distiller's grain biochar immobilized with Lactobacillus plantarum - Guangxu Zhu; Xingfeng Wang; Rongkun Chen; Yunyan Wang; Xingyun Zhao; Panpan Wu; Qiang Tu (Chemical Engineering Journal, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Structural diversity and environmental impacts of Cladophora mats in a large plateau brackish lake - Yuming Wang; Panpan Zhou; Weicheng Zhou; Jinglong Wang; Shun Huang; Hongyi Ao; Chenxi Wu; Genbao Li (Environmental Research, 2025)

Optimizing Cheyletus malaccensis releases for the biocontrol of Liposcelis bostrychophila: Density-dependent efficacy in stored grains - Yiwang Hu; Dingrong Xue; Panpan Zhang; Zhiqi Liu; Zhiyi Fang; Yu Zhang; Yi Wu (Experimental and Applied Acarology, 2025)

Green and sustainable strategy for separation and recovery of high-value fluorine and magnesium from fluorine slag by alkaline roasting-hydrometallurgy - Hang Zhao; Xiaoguang Zhang; Guosai Jiang; Feihua Yang; Yanling Wu; Panpan Mu; Haile Yan; De’an Pan (Journal of Environmental Chemical Engineering, 2025)

Pd-loaded LaNiO3 heterojunctions for efficient CO2 reduction to formaldehyde under infrared light irradiation - Ronald Amoah Gyan; Tong Wu; Panpan Gao; Mohammed Seidu; Zhenghua Ye; Songmei Sun (Journal of Environmental Chemical Engineering, 2025)

Soil rather than root traits drives variation in the rhizosphere microbial community of Pinus taiwanensis in a subtropical mountain ecosystem - Panpan Wu; Dandan Hu; Jun Sun; Jinlong Li; Yimiao Lu; Quanlin Zhong; Dongliang Cheng; James T. Weedon (Applied Soil Ecology, 2025)

Adaptive truncated regularized Newton full-waveform inversion method - Panpan Wu; Meng Ji; Qinglong He (Acta Geophysica, 2025)

Automatic periphyton sampler (APS): A new technique for precise in-situ sampling of periphyton in aquatic environments - Yundong Wu; Wenxuan Zou; Panpan Zhou; Chengrong Peng; Dunhai Li; Genbao Li (Journal of Experimental Marine Biology and Ecology, 2025)

Associations of urinary essential metals and their mixture with metabolic syndrome and its components among Chinese community-dwelling older adults - Panpan Wang; Xuqiu Cheng; Chen Zhang; Jingyuan Lei; Hongli Wang; Yuan Wang; Liang Sun; Bing Hu; Guangbo Qu; Dongmei Zhang; Guimei Chen; Chunmei Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

FengYun-3 meteorological satellites’ microwave radiation Imagers enhance land surface temperature measurements across the diurnal cycle - Yuyang Xiong; Tianjie Zhao; Haishen Lü; Zhiqing Peng; Jingyao Zheng; Yu Bai; Panpan Yao; Peng Guo; Peilin Song; Zushuai Wei; Ronghan Xu; Shengli Wu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Boosting aromatic production from pine sawdust and waste plastics co-pyrolysis via acidity tuning of HZSM-5 - Changsen Zhang; Yupu Xu; Weiwei Wu; Long Ren; Panpan Liu; Tiegang Zhang (Process Safety and Environmental Protection, 2025)

Spiral-structured electrospun conductive conduits filled with aligned nanofibers for peripheral nerve regeneration - Jiahui Song; Siyuan Wu; Chenlong Liao; Zhengchao Yuan; Xiao Yu; Panpan Shang; Yihong Shen; Jie Cui; Jinglei Wu; Binbin Sun; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; et al. (Chemical Engineering Journal, 2025)

Synthesis of covalent organic frameworks with homopore and heteropore in betaine–HFIP based deep eutectic solvents: Application in intelligent colorimetric sensor - Lingling Li; Qiuyi Liu; Dandan Wang; Mingyue Wang; Yu Cai; Yuqiang Xiao; Yue Lan; Jiaqi Hu; Panpan Cheng; Jia Zeng; Zhou Li; Yidong Liu; et al. (Chemical Engineering Journal, 2025)

Pseudostellaria heterophylla cultivar mixtures driven changes in rhizosphere metabolites to suppress soil-borne Fusarium disease - Yuting Liu; Yixuan Zhang; Xingyue Wang; Panpan Dang; Antonino Malacrinò; Jiaoyang Zhang; Zhong Li; Christopher Rensing; Zhongyi Zhang; Wenxiong Lin; Zhen Zhang; Hongmiao Wu (Agriculture, Ecosystems & Environment, 2025)

Achieving efficient photoreduction of CO2 by simultaneously facilitating the splitting of H2O and the conversion of *CO intermediates - Xianghai Song; Gen Li; Xiang Liu; Sheng Xu; Weiqiang Zhou; Zhi Zhu; Mei Wang; Panpan Zhang; Pengwei Huo; Yuanfeng Wu (Chemical Engineering Journal, 2025)

Co-existence of a novel RND efflux pump tmexC6D6.2-toprJ1b and blaOXA-4 in the extensively drug-resistant Pseudomonas aeruginosa ST233 clone - Xuan Wu; Guorong Chen; Panpan Wang; Lu Yang; Yige Wu; Guoquan Wu; Hui Li; Bing Shao (International Journal of Food Microbiology, 2025)

Mechanism and controlling factors of mass transport complexes migration: A case study of the mass transport complexes in the taranaki deep water basin, New Zealand - Yongsheng Zhou; Wei Wu; Jianwei Feng; Guangxu Wang; Aihua Fu; Shiqin Liang; Lulu Wu; Qingchao Li; Weiqing Liu; Zhendong Feng; Changsong Lin; Panpan Chen; et al. (Geomorphology, 2024)

Defining watershed-scale sediment delivery ratio using functional connectivity: Exploring the relationship between monthly-scale sediment delivery ratio and soil erosion — A case study from a karst watershed - Linlv Xiao; Benjin Yu; Rui Li; Panpan Wu; Feiyang Cai (CATENA, 2024)

Changes of vertical distribution of Microcystis colonies driven by short-term rainfall: Disappearance and reformation of surface bloom - Panpan Zhou; Yuming Wang; Yuchen Geng; Yu Zhu; Yundong Wu; Xiaomei Wu; Genbao Li (Journal of Environmental Management, 2024)

Sliding connectors for cyclic construction of steel-UHPC composite truss arch bridges: design method and feasibility study - Guang He; Xudong Shao; Suiwen Wu; Junhui Cao; Panpan Li; Wenyong Cai (Engineering Structures, 2024)

Significant enhancement on diclofenac removal in the Cu(II)/peroxymonosulfate process with neocuproine under neutral pH conditions: Performances, mechanism and anti-interference capability - Zhijie Wu; Zhenming Zhou; Jing Zou; Sheng Li; Jianying Wu; LinFeng He; Shiyi Qiu; Panpan Wang; Jun Ma (Chemical Engineering Journal, 2024)

Estimating spatiotemporal variations of cropland soil organic carbon and its sequestration potential in central China from 1984 to 2019 - Yuanyuan Li; Panpan Ma; Zhenfu Wu; Jie Chen; Yanfeng Zhao (CATENA, 2024)

Dietary hydroxyproline supplementation improves the muscle texture and extends the shelf life of abalone Haliotis discus hannai - Panpan Yue; Peng Chen; Zhenhua Wu; Heng Zhang; Pengfei Zhang; Keke Lei; Hongyang Zhang; Kangsen Mai; Wenbing Zhang (Aquaculture, 2024)

Efficient conversion process and mechanism of bromine in bromine-rich saline wastewater - Jixian Wu; Panpan Mu; Xiaoguang Zhang; Guosai Jiang; Zhe Tan; De'an Pan (Journal of Cleaner Production, 2024)

Preconception mitochondrial DNA copy number plays a crucial role in linking prenatal air pollution with the risk of preterm birth - Qiuming Wang; Yalong Wang; Panpan Sun; Yanan He; Xi Yan; Lifang Jiang; Yuting Zeng; Jingjing Wu; Junxi Zhang; CuiPing Wu; Fangfang Yu; Yue Ba; et al. (International Journal of Hygiene and Environmental Health, 2024)

Ionomer distribution control for improving the performance of proton exchange membrane fuel cells: Insights into structure–property relationships - Jingnan Song; Wutong Zhao; Haibo Wang; Hongjie Meng; Shukai Zhang; Wenkai Zhong; Xuefei Wu; Min Li; Panpan Guan; Ming Zhang; Lei Zhu; Ping He; et al. (Chemical Engineering Journal, 2024)

ERoots: A three-dimensional dynamic growth model of rice roots coupled with soil - Le Yang; Panpan Wu; Zhengkang Zuo; Lan Long; Junlin Shi; Yutang Liu (Biosystems Engineering, 2024)

Protocatechuic acid enhanced the selective degradation of sulfonamide antibiotics in Fe(III)/peracetic acid process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Chenyu Tang; Shiyi Yang; Lingxin Chen; Qingsong Li; Panpan Wang; Jun Ma (Water Research, 2024)

Structure elucidation and antiviral activity of a cold water-extracted mannogalactofucan Ts1-1A from Trametes sanguinea against human cytomegalovirus in vitro - Yiran Wang; Mengxia Yan; Panpan Zhang; Xinna Wu; Siyang Huang; Siru Chen; Yizhou Rong; Yunjie Sheng; Yangyang Wang; Genxiang Mao; Libing Chen; Sanying Wang; et al. (Carbohydrate Polymers, 2024)

Enhanced selective photocatalytic CO2 reduction to CO on AuPd decorated Bi2O2.33 nanosheets - Yupeng Zou; Yidi Shen; Panpan Gao; Tong Wu; Qinlin Zhou; Lei Liu; Xuelian Chen; Songmei Sun; Qi An (Journal of Environmental Chemical Engineering, 2024)

Spongy and anti-pollution MXene/Ag2S/cellulose acetate membrane for sustainable solar-driven interfacial evaporation and water purification - Xue Bai; Qin Wang; Mingzhe Tan; Panpan Zhang; Shiyu Sun; Di Wu; Haoran Mei; Guoqiang Shan; Na Wang; Hongxun Hao; Ting Wang; Xin Huang (Chemical Engineering Journal, 2024)

An ultrasound-triggered injectable sodium alginate scaffold loaded with electrospun microspheres for on-demand drug delivery to accelerate bone defect regeneration - Yin Yi; Jinlin Song; Pengfei Zhou; Yu Shu; Panpan Liang; Huimin Liang; Yanling Liu; Xiaoyan Yuan; Xujia Shan; Xiaohong Wu (Carbohydrate Polymers, 2024)

Divergent intra- and interspecific root order variability identifies a two-dimensional root economics spectrum - Jinlong Li; Xingui Le; Xiaoping Chen; Peter B. Reich; Karl J. Niklas; Xueqin Li; Panpan Wu; Yongjiao Zhou; Quanlin Zhong; Dandan Hu; Dongliang Cheng (Plant and Soil, 2024)

FAM83B regulates mitochondrial metabolism and anti-apoptotic activity in pulmonary adenocarcinoma - Jiajia Wang; Panpan Li; Limin Sun; Jing Zhang; Ke Yue; Yan Wang; Xiaojuan Wu (Apoptosis, 2024)

Abnormal EEG microstates in Alzheimer’s disease: predictors of β-amyloid deposition degree and disease classification - Yibing Yan; Manman Gao; Zhi Geng; Yue Wu; Guixian Xiao; Lu Wang; Xuerui Pang; Chaoyi Yang; Shanshan Zhou; Hongru Li; Panpan Hu; Xingqi Wu; et al. (GeroScience, 2024)
Electroencephalography (EEG) microstates are used to study cognitive processes and brain disease-related changes. However, dysfunctional patterns of microstate dynamics in Alzheimer's disease (AD) remain uncertain. To investigate microstate changes in AD using EEG and assess their association with cognitive function and pathological changes in cerebrospinal fluid (CSF). We enrolled 56 patients with AD and 38 age- and sex-matched healthy controls (HC). All participants underwent various neuropsychological assessments and resting-state EEG recordings. Patients with AD also underwent CSF examinations to assess biomarkers related to the disease. Stepwise regression was used to analyze the relationship between changes in microstate patterns and CSF biomarkers. Receiver operating characteristics analysis was used to assess the potential of these microstate patterns as diagnostic predictors for AD. Compared with HC, patients with AD exhibited longer durations of microstates C and D, along with a decreased occurrence of microstate B. These microstate pattern changes were associated with Stroop Color Word Test and Activities of Daily Living scale scores (all P < 0.05). Mean duration, occurrences of microstate B, and mean occurrence were correlated with CSF Aβ 1–42 levels, while duration of microstate C was correlated with CSF Aβ 1–40 levels in AD (all P < 0.05). EEG microstates are used to predict AD classification with moderate accuracy. Changes in EEG microstate patterns in patients with AD correlate with cognition and disease severity, relate to Aβ deposition, and may be useful predictors for disease classification.

Integrated SEAWAT model and GALDIT method for dynamic vulnerability assessment of coastal aquifer to seawater intrusion - Panpan Lyu; Jian Song; Ziyue Yin; Jianfeng Wu; Jichun Wu (Science of The Total Environment, 2024)

Direct power to hydrogen to power based on solid oxide cells with a high-performance Sr-Ba free air electrode - Panpan Zhang; Jieshan Chang; Yujie Wu; Junmeng Jing; Haoran Wang; Ziwei Zheng; Liyan Chen; Jiaheng Li; Zhibin Yang (Fuel, 2024)

Construction and analysis of the immune effect of two different vaccine types based on Vibrio harveyi VgrG - Xiangyu Du; Minjie Kang; Chunhuan Yang; Xinping Yao; Lvliang Zheng; Ying Wu; Panpan Zhang; Han Zhang; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2024)

Microplastics release from face masks: Characteristics, influential factors, and potential risks - Xu Zhao; Panpan Gao; Ziqing Zhao; Yinghong Wu; Hongwen Sun; Chunguang Liu (Science of The Total Environment, 2024)

Synthesis, characterization and performance evaluation of a nontoxic functional plasticizer for poly(vinyl chloride) derived from sustainable lactic acid - Bingfeng Qian; Panpan Peng; Chenliang Wang; Lijie Wang; Jianan Zhang; Mingyuan Wu; Jiuyi Liu; Qingyun Wu; Jianjun Yang (Journal of Cleaner Production, 2024)

Targeting lncRNA16 by GalNAc-siRNA conjugates facilitates chemotherapeutic sensibilization via the HBB/NDUFAF5/ROS pathway - Yanfang Liu; Yan Wang; Bing Liu; Wenzhong Liu; Yuanyuan Ma; Yiren Cao; Shi Yan; Panpan Zhang; Lixin Zhou; Qimin Zhan; Nan Wu (Science China Life Sciences, 2024)

Long non-coding RNA ENSMUST00000197208 promotes a shift in the Th17/Treg ratio via the P2X7R-NLRP3 inflammasome axis in collagen-induced arthritis - Yuting Pan; Yan Wu; Yingying Liu; Panpan Wang; Hui Huang; Jing Jin; Yuying Fang; Shuoyin Huang; Zhidan Fan; Haiguo Yu (Immunologic Research, 2024)

U-shaped relationship between ozone exposure and preterm birth risk associated with preconception telomere length - Guoyu Zhou; Jian Chai; Qinyang Li; Panpan Sun; Yalong Wang; Jingjing Wu; Junxi Zhang; Yan Li; Wei Dong; Cuican Zhang; Fangfang Yu; Xi Yan; et al. (Environmental Pollution, 2024)

Molecular epidemiology, phenotypic and genomic characterization of antibiotic-resistant enterococcal isolates from diverse farm animals in Xinjiang, China - Wanzhao Chen; Qiaojun Wang; Huimin Wu; Panpan Xia; Rui Tian; Ruichao Li; Lining Xia (Science of The Total Environment, 2024)

Conceptual design and preliminary test of the novel structure of steel inner core-UHPC composite box girder - Panpan Li; Xudong Shao; Suiwen Wu; Wei Fan; Bin Liu; Xudong Zhao (Engineering Structures, 2024)

Crystal defect engineering to construct oxygen vacancies in MXene-derived TiO2 nanocomposites for boosting photocatalytic degradation of 2,4,6-trichlorophenol - Feihong Wang; Qi Zhao; Hongpeng Li; Qiangshun Wu; Luyan Zhang; Yan Li; Liang Qiao; Ye Yuan; Jun Ma; Panpan Wang; Tianming Chen (Chemical Engineering Journal, 2024)

Identification and characterization of human hematopoietic mesoderm - Yuqi Wen; Jingjing Zhao; Runqing Zhang; Fan Liu; Xiaoyuan Chen; Dan Wu; Mengge Wang; Cuicui Liu; Pei Su; Panpan Meng; Yiyue Zhang; Xin Gao; et al. (Science China Life Sciences, 2024)

Bicomponent hydrogel laden with TGF-β3-nucleus pulposus stem cells for disc degeneration repair - Panpan Xu; Linbing Lou; Wanda Zhan; Chaoyong Wang; Shuangshi Wu; Zhengwei Liu; Yongxiang Wang (Chemical Engineering Journal, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Abortion storm of Yili horses is associated with Equus caballus papillomavirus 2 variant infection - Panpan Tong; Nuerlan Palidan; Xiaozhen Song; Shuyao Tian; Lei Zhang; Guiling Wu; Haifeng Deng; Chenyang Jia; Ruli Duan; Youtu Suo; Juanjuan Pan; Yueyi Dang; et al. (Archives of Microbiology, 2024)

Spatial-temporal characteristics of inorganic anions in the Middle Route of South-North Water Diversion project in Henan province (China) - Tailai Yin; Zhenzhen Cui; Panpan Fan; Pengcheng Lan; Xiaojun Wang; Dongyu Wu; Han Liu; Zhaojin Chen; Yuying Li; Bailian Li (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Surface regulating of copper-iron nanoparticles bimetallic exsolution for enhanced performance and durability of double perovskite anode in solid oxide fuel cells - Yujie Wu; Shuai Wang; PanPan Zhang; Xu Han; Hongfei Chen; Bo Wei; Zhe Lü (Fuel, 2023)

Analysis on the salt tolerance of Nitraria sibirica Pall. based on Pacbio full-length transcriptome sequencing - Panpan Zhang; Fengxiang Zhang; Zhiheng Wu; Sunaer Cahaeraduqin; Wei Liu; Yongqing Yan (Plant Cell Reports, 2023)

High-efficiency genetic engineering toolkit for virus based on lambda red-mediated recombination - Jing Yi; Maifei Zhang; Lin Zhu; Changzhi Xu; Binglin Li; Panpan Wu; Hang Wu; Buchang Zhang (Biotechnology Letters, 2023)

Promoting effect and mechanism of residual feed organic matter on the formation of cyanobacterial blooms in aquaculture waters - Jinglong Wang; Weicheng Zhou; Shun Huang; Xiaomei Wu; Panpan Zhou; Yuchen Geng; Yu Zhu; Yuming Wang; Yundong Wu; Qinyi Chen; Yuang Ding; Zhicong Wang; et al. (Journal of Cleaner Production, 2023)

3D lithiophilic framework fixed on the surface of LLZTO solid electrolyte shaping the contact between Li metal and ceramic - Yuhao Shi; Yifei Cai; Jiaqi Zhao; Tong Wu; Xiaoqian Xue; Tiesong Lin; Panpan Lin; Ce Wang; He Peng (Chemical Engineering Journal, 2023)

CgPG21 is involved in the degradation of the cell wall during the secretory cavity formation in Citrus grandis ‘Tomentosa’ fruits - Mei Bai; Panpan Tong; Qun Luo; Na Shang; Hailan Huang; Bin Huai; Hong Wu (Plant Cell Reports, 2023)

The allocation of anatomical traits determines the trade-off between fine root resource acquisition–transport function - Jinlong Li; Xingui Le; Xiaoping Chen; Karl J. Niklas; Xueqin Li; Panpan Wu; Yongjiao Zhou; Quanlin Zhong; Dandan Hu; Dongliang Cheng (Oecologia, 2023)

Dietary advanced glycation end products (dAGEs): An insight between modern diet and health - Zhaoqing Tian; Shasha Chen; Yiheng Shi; Panpan Wang; Yongning Wu; Guoliang Li (Food Chemistry, 2023)

Biomineralization-inspired artificial clickase for portable click SERS immunoassay of Salmonella enterica serovar Paratyphi B in foods - Xianlong Zhang; Yiheng Shi; Panpan Wang; Di Wu; Jianghua Liu; Rui Huang; Yongning Wu; Guoliang Li (Food Chemistry, 2023)

CpG ODN 1668 as TLR9 agonist mediates humpback grouper (Cromileptes altivelis) antibacterial immune responses - Xiaojuan Chen; Panpan Zhang; Pengshuo Li; Guotao Wang; Jianlong Li; Ying Wu; Zhenjie Cao; Yongcan Zhou; Yun Sun (Fish & Shellfish Immunology, 2023)

High-throughput imprinted non-metal S-scheme heterojunction self-cleaning membrane with tight adhesion via dopamine for selective photodegradation of TC - Ziyang Lu; Yewei Ren; Panpan Wang; Yangrui Xu; Jutao Zhang; Binghui Wei; Guosheng Zhou; Xinlin Liu; Yongqiang Huang; Chundu Wu (Journal of Environmental Chemical Engineering, 2023)

Visible-light photocatalysis degradation of enrofloxacin by crawfish shell biochar combined with g-C3N4: Effects and mechanisms - Longqu Xiao; Shiyang Zhang; Boqi Chen; Panpan Wu; Ningdong Feng; Feng Deng; Zhi Wang (Journal of Environmental Chemical Engineering, 2023)

Gravity disturbance compensation for dual-axis rotary modulation inertial navigation system - Panpan Zhang; Lin Wu; Lifeng Bao; Bo Wang; Hui Liu; Qianqian Li; Yong Wang (Frontiers in Marine Science, 2023)
Gravity disturbance compensation is an important technique for improving the positioning accuracy of high-precision inertial navigation systems (INS). Aiming at the current problems of the resolution of gravity compensation background field and the robustness of gravity compensation algorithm are insufficient for gravity compensation. In this study, the error and frequency characteristics of INS caused by gravity disturbances are investigated. The gravity disturbance with a spatial resolution of 1’ × 1’ from a high-precision satellite altimetry marine gravity field model is preliminarily introduced into the initial alignment and pure INS calculation to implement the gravity compensation of the dual-axis rotary modulation INS. Detailed calculation results show that the east gravity disturbance affects the north attitude, and the north gravity disturbance affects the east attitude in the initial alignment. In the pure INS calculation, the horizontal gravity disturbance causes a navigation error in the form of Schuler oscillation. The INS navigation error caused by horizontal gravity disturbance is mainly affected by its amplitude; however, the horizontal gravity disturbance accuracy from the satellite altimetry model for INS gravity compensation can be ignored in practice. In addition, for low-speed underwater vehicles, the influence of high-frequency gravity disturbance signals on the INS position shows an increasing trend. Finally, the effectiveness of the gravity compensation achieved by the horizontal gravity disturbance from the satellite altimeter model is confirmed by a dynamic shipborne test. The positioning accuracy of the rotary modulation INS is maximally improved by approximately 17.9% after the horizontal gravity disturbance is compensated simultaneously in the pure INS calculation and the initial alignment.

Bioactive hydrogel encapsulated dual-gene engineered nucleus pulposus stem cells towards intervertebral disc tissue repair - Yuchen Ye; Panpan Xu; Cai Li; Shichang Jin; Jie Hu; Yuekun Fang; Kun Zhu; Gang Xu; Zhongbing Han; Zhili Zhang; Nan Wu; Pan Jiang; et al. (Chemical Engineering Journal, 2023)

Novel biodegradation pathway of insecticide flonicamid mediated by an amidase and its unusual substrate spectrum - Huoyong Jiang; Panpan Yuan; Jianjun Ding; Hongkai Wu; Li Wang; Kexin Chen; Nengdang Jiang; Yijun Dai (Journal of Hazardous Materials, 2023)

Enhanced removal of hexavalent chromium and nitrate in aquifers by alkali-modified emulsified vegetable oil - Linjie Ding; Huanhuan Wu; Jiansen Lei; Panpan Li; Lina Wang (Journal of Cleaner Production, 2023)

Stimulating Zn2+ permselectivity for prominent zinc anode reversibility by designing a self-assembled artificial layer - Panpan Wang; Bin Sun; Xiaolin Wei; Liwen Yang; Hui Wu (Chemical Engineering Journal, 2023)

Structure, stability, antioxidant activity, and controlled-release of selenium nanoparticles decorated with lichenan from Usnea longissima - Ziying Yang; Yajie Hu; Panpan Yue; Huiling Li; Yuying Wu; Xiang Hao; Feng Peng (Carbohydrate Polymers, 2023)

Establishment of a Ca(II) ion-quantum dots fluorescence signal amplification sensor for high-sensitivity biomarker detection - Yanbing Lv; Panpan Wang; Jinjie Li; Ning Li; Dangdang Xu; Ruili Wu; Huaibin Shen; Lin Song Li (Analytica Chimica Acta, 2023)

High frequency sequence stratigraphy analysis for Dawangbei subsag based on the spectrum analysis of the logging curve - Xue Zhiyuan; Chen Panpan; Li Cunlei; Dai Kewen; Zhu Jingwei; Wu Yonggang (Arabian Journal of Geosciences, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Strigolactone is involved in nitric oxide-enhanced the salt resistance in tomato seedlings - Huwei Liu; Changxia Li; Mei Yan; Zongxi Zhao; Panpan Huang; Lijuan Wei; Xuetong Wu; Chunlei Wang; Weibiao Liao (Journal of Plant Research, 2022)

Dental Pulp Stem Cell-Derived Extracellular Vesicles Mitigate Haematopoietic Damage after Radiation - Fanxuan Kong; Chu-Tse Wu; Panpan Geng; Chao Liu; Fengjun Xiao; Li-Sheng Wang; Hua Wang (Stem Cell Reviews and Reports, 2021)
Radiation therapy can cause haematopoietic damage, and mesenchymal stem cells (MSCs) derived extracellular vesicles (EVs) have been shown to reverse this damage. Our previous research showed that dental pulp stem cells (DPSCs) have a strong proliferation capacity and can produce abundant amounts of EVs to meet the requirements for use in vitro and in vivo. DPSCs derived EVs (DPSCs-EVs) are evaluated for their effect on reducing haematopoietic damage. Haematopoietic stem cell (HSC) numbers and function were assessed by flow cytometry, peripheral blood cell counts, histology and bone marrow transplantation. Epidermal growth factor (EGF) was used as a reference for evaluating the efficiency of EVs. miRNA microarray was employed to find out the changes of miRNA expression after cells being irradiated in vivo and the role they may play in mitigation the radiation caused injury. We observed the effect of DPSCs-EVs on promoting proliferation and inhibiting apoptosis of human umbilical vein endothelial cells (HUVECs) and FDC-P1 cells in vitro. We found that DPSCs-EVs and EGF could comparably inhibit the decrease in WBC, CFU count and KSL cells in vivo. We also verified that EVs could accelerate the recovery of long-term HSCs. In summary, DPSCs-EVs showed an apoptosis resistant effect on HUVECs and FDC-P1 cells after radiation injury in vitro. EVs from DPSCs were comparable to EGF in their ability to regulate haematopoietic regeneration after radiation injury in vivo. Radiation could alter the expression of some miRNAs in bone marrow cells, and EVs could correct these changes to some extent.

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Successive digestion of tilapia collagen by serine proteinase and proline specific endopeptidase to produce novel angiotensin I-converting enzyme inhibitory peptides - Xin Hua; Lechang Sun; Chan Zhong; Qiang Wu; Panpan Xiao; Asami Yoshida; Guangming Liu; Minjie Cao (Marine Life Science & Technology, 2020)

Edaravone at high concentrations attenuates cognitive dysfunctions induced by abdominal surgery under general anesthesia in aged mice - Yiying Zhou; Xiang Wu; Luying Ye; Yujing Bai; Hui Zhang; Zhenquan Xuan; Yi Feng; Panpan Zhang; Yi Chen; Yushan Yan; Binbin Zhu; Wei Cui (Metabolic Brain Disease, 2020)

Neonatal exposure to organophosphorus flame retardant TDCPP elicits neurotoxicity in mouse hippocampus via microglia-mediated inflammation in vivo and in vitro - Xiali Zhong; Jingwei Wu; Weijian Ke; Yuejin Yu; Di Ji; Jianmeng Kang; Jiahuang Qiu; Can Wang; Panpan Yu; Yanhong Wei (Archives of Toxicology, 2020)

Molecular characterization of a novel TaGL3-5A allele and its association with grain length in wheat (Triticum aestivum L.) - Jian Yang; Yanjie Zhou; Qiuhong Wu; Yongxing Chen; Panpan Zhang; Yu’e Zhang; Weiguo Hu; Xicheng Wang; Hong Zhao; Lingli Dong; Jun Han; Zhiyong Liu; et al. (Theoretical and Applied Genetics, 2019)

Porcine circovirus type 2 ORF5 protein induces endoplasmic reticulum stress and unfolded protein response in porcine alveolar macrophages - Yueling Ouyang; Lei Xu; Jiangman Lv; Yufeng Hou; Zhixin Fan; Panpan Xu; Yanfen Jiang; Mengmeng Wu; Ran Li; Yanming Zhang; Kangkang Guo (Archives of Virology, 2019)

Comparison and combination of selective grazing on natural seston by benthic bivalves (Hyriopsis cumingii) and pelagic fish (Hypophthalmichthys molitrix) - Long Wang; Panpan Liu; Jian Sun; Yi Zhang; Qiaohong Zhou; Zhenbin Wu; Feng He (Environmental Science and Pollution Research, 2018)

Sexual specific functions of Tub1 beta‐tubulins require stage‐specific RNA processing and expression in Fusarium graminearum - Daipeng Chen; Chunlan Wu; Chaofeng Hao; Panpan Huang; Huiquan Liu; Zhuyun Bian; Jin‐Rong Xu (Environmental Microbiology, 2018)
Summary The wheat head blight fungus Fusarium graminearum has two highly similar beta‐tubulin genes with overlapping functions during vegetative growth but only TUB1 is important for sexual reproduction. To better understand their functional divergence during ascosporogenesis, in this study we characterized the sequence elements important for stage‐specific functions of TUB1. Deletion of TUB1 blocked the late but not initial stages of perithecium formation. Perithecia formed by tub1 mutant had limited ascogenous hyphae and failed to develop asci. Silencing of TUB1 by MSUD also resulted in defects in ascospore formation. Interestingly, the 3′‐UTR of TUB1 was dispensable for growth but essential for its function during sexual reproduction. RIP mutations that specifically affected Tub1 functions during sexual reproduction also were identified in two ascospore progeny. Furthermore, site‐directed mutagenesis showed that whereas the non‐editable mutations at three A‐to‐I RNA editing sites had no effects, the N347D (not T362D or I368V) edited mutation affected ascospore development. In addition, the F167Y, but not E198K or F200Y, mutation in TUB1 conferred tolerance to carbendazim and caused a minor defect in sexual reproduction. Taken together, our data indicate TUB1 plays an essential role in ascosporogenesis and sexual‐specific functions of TUB1 require stage‐specific RNA processing and Tub1 expression.

Engineering genome-reduced Bacillus subtilis for acetoin production from xylose - Panpan Yan; Yuanqing Wu; Li Yang; Zhiwen Wang; Tao Chen (Biotechnology Letters, 2018)

Effect of mechanical degradation of laminated elastomeric bearings and shear keys upon seismic behaviors of small-to-medium-span highway bridges in transverse direction - Gang Wu; Kehai Wang; Panpan Zhang; Guanya Lu (Earthquake Engineering and Engineering Vibration, 2018)

Retraction Note to: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2017)

Antibacterial activity of Pyrrosia petiolosa ethyl acetate extract against Staphylococcus aureus by decreasing hla and sea virulence genes - Liju Song; Mei Cao; Chong Chen; Panpan Qi; Ningzhe Li; Daoyan Wu; Jingshan Peng; Xuege Wang; Mao Zhang; Guoku Hu; Jian Zhao (Natural Product Research, 2017)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

RETRACTED ARTICLE: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2016)

Association between polymorphisms in the promoter region of interleukin-10 and susceptibility to inflammatory bowel disease - Hongchao Lv; Yongshuai Jiang; Jin Li; Mingming Zhang; Zhenwei Shang; Jiajia Zheng; Xin Wu; Panpan Liu; Ruijie Zhang; Huimin Yu (Molecular Biology Reports, 2014)

Loop-mediated isothermal amplification for rapid and convenient detection of Mycoplasma hyopneumoniae - Jiahe Li; F. Chris Minion; Andrew C. Petersen; Fei Jiang; Sheng Yang; Panpan Guo; Jinxiang Li; Wenxue Wu (World Journal of Microbiology and Biotechnology, 2013)